(untitled) (International Journal of Engineering and Computer Science, 2017)
The protection afforded to an automated information system in order to attain the applicable objectives of preserving the integrity, availability and confidentiality of information system resources is called computer security. Integrity of a message should be preserved as it travels from the sender to the recipient, it is compromised if the message is modified during transit. The principle of availability states the resources should be available to authorized parties at all times. The principle of confidentially specifies that only the sender and the intended recipient should be able to access the contents of a message. Data security is a very vital thing to ensure the privacy of a user from others. For an organization, it is very necessary to keep the information safe from various attackers. Computer and network security is a battle of wits between a perpetrator who tries to find holes and the designer or administrator who tries to close them. Strong encryption algorithms can be used to make it impossible for an attacker to attack the node that is strongly protected by multiple keys. This work is focused on the use of dynamic keys for securing the data and for securing data transmission